2021
DOI: 10.3389/fbioe.2021.734068
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-Coil Based Inclusion Bodies and Their Potential Applications

Abstract: The production of recombinant proteins using microbial cell factories is frequently associated with the formation of inclusion bodies (IBs). These proteinaceous entities can be sometimes a reservoir of stable and active protein, might display good biocompatibility, and are produced efficiently and cost-effectively. Thus, these submicrometric particles are increasingly exploited as functional biomaterials for biotechnological and biomedical purposes. The fusion of aggregation-prone sequences to the target prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…ccNPs are reminiscent of bacterial inclusion bodies (IBs) but differ in their assembly mechanism. Unlike conventional IBs, ccNPs are not sustained by the formation of intermolecular β-sheets of an amyloid-like nature between misfolded and thus mostly inactive polypeptide chains, but instead by the assembly of native α-helical structures, which are not expected to significantly impact the fold of the adjacent proteins . Consistent with this view, purified ccNPs are highly fluorescent and display fluorescence excitation and emission spectra equivalent to those of native GFP (Figure f,g).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…ccNPs are reminiscent of bacterial inclusion bodies (IBs) but differ in their assembly mechanism. Unlike conventional IBs, ccNPs are not sustained by the formation of intermolecular β-sheets of an amyloid-like nature between misfolded and thus mostly inactive polypeptide chains, but instead by the assembly of native α-helical structures, which are not expected to significantly impact the fold of the adjacent proteins . Consistent with this view, purified ccNPs are highly fluorescent and display fluorescence excitation and emission spectra equivalent to those of native GFP (Figure f,g).…”
Section: Resultsmentioning
confidence: 52%
“…Unlike conventional IBs, ccNPs are not sustained by the formation of intermolecular βsheets of an amyloid-like nature between misfolded and thus mostly inactive polypeptide chains, 28 but instead by the assembly of native α-helical structures, which are not expected to significantly impact the fold of the adjacent proteins. 29 Consistent with this view, purified ccNPs are highly fluorescent and display fluorescence excitation and emission spectra equivalent to those of native GFP (Figure 2f,g). Additionally, the Fourier transform infrared (FTIR) spectroscopy spectrum in the in the amide I region (1600−1700 cm −1 ) show a dominant signal at 1648 cm −1 , which can be attributed to the α-helical structures of the ZapB and Z domains, and which is absent or minor in conventional IBs 30 (Figure 2h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Due to their heterogenous nature, the structures of IBs and CatIBs are difficult to access, but studies using different spectroscopic methods have shown that their internal structure also depends on the aggregation inducing tags and can possess or be devoid of amyloid-like structures [96], and can contain a variable degree of unfolded polypeptides alongside natively folded protein [97][98][99]. Like IBs, CatIBs can easily be obtained by simple heterologous production in, e.g., E.coli, cell lysis and subsequent centrifugation and washing steps, yielding relatively pure (up to 90 % target protein) preparations (Fig.…”
Section: Catalytically Active Inclusion Bodiesmentioning
confidence: 99%
“…Enzyme immobilization confines the soluble enzymes on insoluble carriers through physical or chemical methods. , Considering that the catalytic performance of enzymes is also impacted by the properties of carrier materials and the roles of chemical reagents, the laborious screening for suitable carriers or chemical reagents is always indispensable. To facilitate the immobilization process, many molecular immobilization strategies have been proposed recently. In particular, many auto-assembly tags such as 18A, ELK16, L6KD, GFIL8, NSPdoT, HVdoT, and DMdoT have been developed for triggering the self-assembly of enzymes in vivo . Recently, Wang et al reported CipA and CipB from Photorhabdus luminescens as universal scaffolds for organizing enzymes into protein crystalline inclusions (PCIs) by N-terminal fusion .…”
Section: Introductionmentioning
confidence: 99%